'Why does it happen like this?' Consulting with users and providers prior to an evaluation of services for children with life limiting conditions and their families. (September 2015) - Hunt, Anne; Brown, Erica; Coad, Jane; Staniszewska, Sophie; Hacking, Suzanne; Chesworth, Brigit; Chambers, Lizzie
Children with life limiting conditions and their families have complex needs. Evaluations must consider their views and perspectives to ensure care is relevant, appropriate and acceptable. We consulted with children, young people, their parents and local professionals to gain a more informed picture of issues affecting them prior to preparing a bid to evaluate services in the area. Multiple methods included focus groups, face-to-face and telephone interviews and participatory activities. Recordings and products from activities were analysed for content to identify areas of relevance and concern. An overarching theme from parents was 'Why does it happen like this?' Services did not seem designed to meet their needs. Whilst children and young people expressed ideas related to quality of environment, services and social life, professionals focused on ways of meeting the families' needs. The theme that linked families' concerns with those of professionals was 'assessing individual needs'. Two questions to be addressed by the evaluation are (1) to what extent are services designed to meet the needs of children and families and (2) to what extent are children, young people and their families consulted about what they need? Consultations with families and service providers encouraged us to continue their involvement as partners in the evaluation.